2010
DOI: 10.1021/am100363d
|View full text |Cite
|
Sign up to set email alerts
|

Ag−TiO2 Nanoparticle Codoped SiO2 Films on ZrO2 Barrier-Coated Glass Substrates with Antibacterial Activity in Ambient Condition

Abstract: Anatase TiO2 and Ag nanoparticles (NPs) codoped SiO2 films were prepared by the sol-gel method. Proportionate amounts of 3-(glycidoxypropyl)trimethoxysilane (GLYMO), tetraethylorthosilicate (TEOS) and 3-(methacryloxypropyl)trimethoxysilane (MEMO) derived inorganic-organic silica sol, commercially available dispersed anatase TiO2 NPs, and AgNO3 were used to prepare the sols. The films were prepared on ZrO2 (cubic) precoated soda-lime glass substrates by a single-dipping technique and heat-treated at 450 °C in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…The mixed phases of TiO 2 can usually retard the antibacterial as well as photocatalytic properties, and hence, it needs to consider the best catalytic phase of supportive TiO 2 materials for the synergetic enhancement of antibacterial activity. Similarly, Ag‐TiO 2 co‐doped SiO 2 films are prepared by dipping technique . The dipping technique usually results the nonuniform film formations as the nucleation particles diverting toward the bottom of the reaction mixture and hence nonuniform thickness of thin film results lower antibacterial activity due to the improper interactions with bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed phases of TiO 2 can usually retard the antibacterial as well as photocatalytic properties, and hence, it needs to consider the best catalytic phase of supportive TiO 2 materials for the synergetic enhancement of antibacterial activity. Similarly, Ag‐TiO 2 co‐doped SiO 2 films are prepared by dipping technique . The dipping technique usually results the nonuniform film formations as the nucleation particles diverting toward the bottom of the reaction mixture and hence nonuniform thickness of thin film results lower antibacterial activity due to the improper interactions with bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Ag-doped titania coatings were significantly more photocatalytically and antimicrobial active than a titania coating. Mukhopadhyay et al 16 developed Ag-TiO 2 nanoparticles codoped SiO 2 films on crystalline ZrO 2 barrier-coated soda-lime glass substrates. The presence of presynthesized anatase nanoparticles helped the silver stabilization and improved the overall antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Ag‐doped titania coatings were significantly more photocatalytically and antimicrobial active than a titania coating. Mukhopadhyay et al . developed Ag–TiO 2 nanoparticles codoped SiO 2 films on crystalline ZrO 2 barrier‐coated soda‐lime glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 has been shown to possess photoactivated bactericidal properties, especially under blue or UV light. Under ultraviolet irradiation, TiO 2 generates many ROS including hydroxl radicals, superoxide, and hydrogen peroxide that disrupt the cell walls of bacteria and inhibit their respiratory system ( Mukhopadhyay, Basak et al, 2010 ; Verdier, Coutand et al, 2014 ). Nevertheless, because of the fast rate of electron-hole recombination within TiO 2 , the ROS production is limited ( Nino-Martinez, Martinez-Castanon et al, 2008 ).…”
Section: Cellulose-based Nanofibrils Against Bacterial Infectionsmentioning
confidence: 99%